167k views
1 vote
SQ bisects RST, and RSQ = 2x-4. Write an expression for RST.

Slect an answer:

4x – 8

4x – 4

2x – 4

x – 2

SQ bisects RST, and RSQ = 2x-4. Write an expression for RST. Slect an answer: 4x – 8 4x-example-1
User NFT Master
by
5.5k points

2 Answers

2 votes

4x - 8 ← first in list

Since SQ bisects ∠RST then ∠RSQ = ∠QST = 2x - 4

∠RST = ∠RST + ∠QST

∠RST = 2x - 4 + 2x - 4 = 4x - 8


User Attila Fulop
by
5.4k points
2 votes

Answer:

4x - 8

Explanation:

... ∠RST = ∠RSQ + ∠QST

Since SQ bisects ∠RST, that means ...

... ∠RSQ = ∠QST

Using this fact in the first equation, we have

... ∠RST = ∠RSQ + ∠RSQ = 2×∠RSQ

Using the given expression for ∠RSQ, we have

... ∠RST = 2×(2x-4) = 4x - 8

User Jtth
by
5.4k points